Cases in commercial bank management - Marks, Leonard; Coleman, Alan B. (New York : McGraw-Hill, 1962)
The book examines cases in commercial banking as it relates to bank management, managing reserves, credit information and analysis as well unsecured loans. It is the result of the authors efforts to collect teaching materials for the course on commercial banking.
asm; 14/11/2019
Loans
Keywords: Banks and banking